The role of technology in business to consumer E-commerce evidence from Asia. ([Manila] Asian Development Bank, 2021)
Governments can consider these findings as important issues in building an enabling environment for the development of B2C online commerce.
Keywords: Information technology; Financial institution; Electronic books